Do you know this syndrome? Werner syndrome - Özlem Bilgiç (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Werner syndrome is a rare autosomal recessive disorder, caused by mutations in the WRN gene. Clinical findings include: senile appearance, short stature, grey hair, alopecia, bird-like face, scleroderma-like skin changes, skin ulcers, voice abnormalities, cataracts, osteoporosis, type 2 diabetes mellitus, ischemic heart disease and hypogonadism. The syndrome begins to become apparent in adolescence but it is usually diagnosed in the third or fourth decade of life. Since the patients usually die by the age of 40-50 years related to malignant neoplasms or atherosclerotic complications, they should be closely followed and treated for complications